Role of androgen receptor CAG repeat polymorphism and X-inactivation in the manifestation of recurrent spontaneous abortions in Indian women. - Meka Aruna (Public Library of Science (PLoS), 2011)
The aim of the present study was to investigate the role of CAG repeat polymorphism and X-chromosome Inactivation (XCI) pattern in Recurrent Spontaneous Abortions among Indian women which has not been hitherto explored. 117 RSA cases and 224 Controls were included in the study. Cases were recruited from two different hospitals--Lakshmi Fertility Clinic, Nellore and Fernandez Maternity Hospital, Hyderabad. Controls were roughly matched for age, ethnicity and socioeconomic status. The CAG repeats of the Androgen Receptor gene were genotyped using a PCR-based assay and were analysed using the GeneMapper software to determine the CAG repeat length. XCI analysis was also carried out to assess the inactivation percentages. RSA cases had a significantly greater frequency of allele sizes in the polymorphic range above 19 repeats (p = 0.006), which is the median value of the controls, and in the biallelic mean range above 21 repeats (p = 0.002). We found no evidence of abnormal incidence of skewed X-inactivation. We conclude that longer CAG repeat lengths are associated with increased odds for RSA with statistical power estimated to be ∼90%.